The Acquisition of German Syntax by Spanish-speaking advanced learners based on an underlying Subject Verb Object order - Grümpel, Claudia (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper focuses on the acquisition of word order in German by adult native speakers of Spanish in an institutional context. During three semesters we analyzed the written production of Spanish undergraduate students at intermediate and advanced levels. We contrasted the production of students whose acquisition took place exclusively in Spain with other students who spent one semester at a German University. In addition to this longitudinal corpus, three transversal tests were carried out on our subjects, and then these results were contrasted with those of native German speakers.